MODERN ESTIMATION AND TRENDS OF HUMAN CAPITAL DEVELOPMENT IN TATARSTAN REPUBLIC: THEORY AND PRACTICE - T. A. Sharifullina (Russian Journal of Economics and Law, 2012)
The article views the modern concepts of human capital reproduction and the need to compensate its loss. The economic system is described, in which the source of losses is the expenses for the labor force reproduction within its cost and its part which is determined by the labor force price or its cost.